Risk factors and mortality in the Carbapenem-resistant Klebsiella pneumoniae infection: case control study. (16th November 2016) - Akgul, Fethiye; Bozkurt, Ilkay; Sunbul, Mustafa; Esen, Saban; Leblebicioglu, Hakan
Abstract : Carbapenem-resistant Klebsiella pneumoniae (CRKP) has been known as a nosocomial pathogen, both for the last 10 years in Turkey and for 20 years worldwide. Due to limited treatment options and high mortality rates, despite improvements in the field of medicine at the present time, CRKP is still a big threat for public health. This study was carried out between the dates of January 2010 and September 2014. Patients ≥18 who were hospitalized for at least 72 h and who also had CRKP growth were included in the study as a case group. In the same period patients, who were hospitalized in the same ward and did not have CRKP growth were selected as the control group. It was determined that no glycopeptides and steroids use nor tracheostomy as protective factors would be employed in terms of non-development of CRKP. Mechanical ventilation, tracheostomy, urinary catheter presence, central venous catheterization, nasogastric tube placement, advanced age, acute renal insufficiency, total parenteral nutrition, carbapenem, glycopeptide, and piperacillin tazobactam were all detected as risk factors in terms of CRKP infection development. As a result, rational usage of antibiotics for preventing infections developing with CRKP should be targeted.